Nanolayer-like-shaped MgFe2O4 synthesised via a simple hydrothermal method and its catalytic effect on the hydrogen storage properties of MgH2. Issue 28 (25th April 2018) - Ali, N. A.; Idris, Nurul Hayati; Din, M. F. Md; Mustafa, N. S.; Sazelee, N. A.; Halim Yap, F. A.; Sulaiman, N. N.; Yahya, M. S.; Ismail, M.
Abstract : The nanolayer-like-shaped MgFe2 O4 -added MgH2 composite showed an improvement in de/absorption properties compared to that of un-doped MgH2 . Abstract : In this study, the effect of nanolayer-like-shaped MgFe2 O4 that is synthesised via a simple hydrothermal method on the performance of MgH2 for hydrogen storage is studied. MgH2 + 10 wt% MgFe2 O4 is prepared by using the ball milling method. The MgFe2 O4 -doped MgH2 sample started to release H2 at approximately 250 °C, 90 °C and 170 °C lower than the milled and pure MgH2 respectively. At 320 °C, the isothermal desorption kinetic study has shown that the doped sample has desorbed approximately 4.8 wt% H2 in 10 min while the milled MgH2 desorbed less than 1.0 wt% H2 . For isothermal absorption kinetics, the doped sample can absorb approximately 5.5 wt% H2 in 10 min at 200 °C. Meanwhile, the undoped sample absorbs only 4.0 wt% H2 in the same condition. The activation energy of 10 wt% MgFe2 O4 -doped MgH2 composite is 99.9 kJ mol −1, which shows a reduction of 33.1 kJ mol −1 compared to the milled MgH2 (133.0 kJ mol −1 ). X-ray diffraction spectra display the formation of new species which are Fe and MgO after dehydrogenation, and these new species are believed to act as the real catalyst that plays a crucial role in improving the sorption performance of the MgFe2 O4 -doped MgH2 system by providing a synergetic catalytic effect.